2015
DOI: 10.1097/md.0000000000001097
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol Reduces Cancer Risk

Abstract: Abstractβ-Blockers have been reported to exhibit potential anticancer effects in cancer cell lines and animal models. However, clinical studies have yielded inconsistent results regarding cancer outcomes and cancer risk when β-blockers were used. This study investigated the association between propranolol and cancer risk.Between January 1, 2000 and December 31, 2011, a patient cohort was extracted from the Longitudinal Health Insurance Database 2000, a subset of the Taiwan National Health Insurance Research Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 36 publications
2
65
0
1
Order By: Relevance
“…Propranolol, a non-selective antagonist of beta-adrenoceptors, is suggested to reduce disease progression in different cancer types [6, 7, 39–43]. Because of its dramatic efficacy in the involution of infantile hemangioma [44], it has been proposed that propranolol affects tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol, a non-selective antagonist of beta-adrenoceptors, is suggested to reduce disease progression in different cancer types [6, 7, 39–43]. Because of its dramatic efficacy in the involution of infantile hemangioma [44], it has been proposed that propranolol affects tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hepatitis C associated cirrhosis Nkontchou et al reported that PRO use was associated with a decreased risk hepatocellular carcinoma (HCC), with a hazard ratio (HR) = 0.25; (95% CI = 0.09 – 0.65; P < 0.004) [75]. Chang et al published a large cohort study of over 24 238 patients, with a PRO group (> 6 months use, n = 12 119) compared to a non-PRO use group (n = 12 119) over a 12 year period [76]. Overall the risk of cancer was lower in the PRO group (HR = 0.75; 95% CI = 0.67–0.85; P < 0.001), and site specific analysis showed a decreased risk in head and neck cancers (HR = 0.58; 95% CI = 0.35–0.95), oesophagus (HR = 0.35; 95% CI = 0.13 – 0.96), stomach (HR = 0.54; 95% CI = 0.30 – 0.98), colon (HR = 0.68; 95% CI = 0.49 – 0.93), and prostate cancers (HR = 0.52; 95% CI = 0.33 – 0.83).…”
Section: Human Datamentioning
confidence: 99%
“…Some studies reported that NSBB was not associated with increased mortality among decompensated cirrhotic patients with ascites [6][7][8][9], whereas Kalambokis GN, et al [10] found that an increased mortality was observed in Child-Pugh C cirrhotic patients with ascites if using NSBB for more than six months. Moreover, NSBB could reduce cancer risk [11,12], including hepatocellular carcinoma (HCC) [13,14]. The issue about the use of NSBB on the prognosis in compensated cirrhotic patients without major complications has seldom been reported.…”
Section: Introductionmentioning
confidence: 99%